Declining mortality of cerebral venous sinus thrombosis with thrombocytopenia after SARS‐CoV‐2 vaccination. (1st October 2021) - van de Munckhof, Anita; Krzywicka, Katarzyna; Aguiar de Sousa, Diana; Sánchez van Kammen, Mayte; Heldner, Mirjam R.; Jood, Katarina; Lindgren, Erik; Tatlisumak, Turgut; Putaala, Jukka; Kremer Hovinga, Johanna A.; Middeldorp, Saskia; Levi, Marcel; et al.
Abstract: Background and purpose: High mortality rates have been reported in patients with cerebral venous sinus thrombosis (CVST) due to vaccine‐induced immune thrombotic thrombocytopenia (VITT) after vaccination with adenoviral vector SARS‐CoV‐2 vaccines. The aim of this study was to evaluate whether the mortality of patients with CVST‐VITT has decreased over time. Methods: The EudraVigilance database of the European Medicines Agency was used to identify cases of CVST with concomitant thrombocytopenia occurring within 28 days of SARS‐CoV‐2 vaccination. Vaccines were grouped based on vaccine type (adenoviral or mRNA). Cases with CVST onset until 28 March were compared to cases after 28 March 2021, which was the day when the first scientific paper on VITT was published. Results: In total, 270 cases of CVST with thrombocytopenia were identified, of which 266 (99%) occurred after adenoviral vector SARS‐CoV‐2 vaccination (ChAdOx1 nCoV‐19, n = 243; Ad26.COV2.S, n = 23). The reported mortality amongst adenoviral cases with onset up to 28 March 2021 was 47/99 (47%, 95% confidence interval 37%–58%) compared to 36/167 (22%, 95% confidence interval 16%–29%) in cases with onset after 28 March ( p < 0.001). None of the four cases of CVST with thrombocytopenia occurring after mRNA vaccination died. Conclusion: The reported mortality of CVST with thrombocytopenia after vaccination with adenoviral vector‐based SARS‐CoV‐2 vaccines has significantly decreased over time, which may indicate a beneficial effect of earlier recognition and/or improved treatment on outcome after VITT. Abstract : The EudraVigilance database of the European Medicines Agency was used to identify cases of cerebral venous sinus thrombosis (CVST) with concomitant thrombocytopenia occurring within 28 days of SARS‐CoV‐2 vaccination. The reported mortality of CVST with thrombocytopenia after vaccination with adenoviral vector‐based vaccines significantly decreased over time with a mortality rate of 47% (95% confidence interval 37%–58%) in cases with CVST onset prior to 28 March 2021 compared to 22% (95% confidence interval 16%–29%) in cases after 28 March ( p < 0.001). This declining mortality may indicate a beneficial effect of earlier recognition and/or improved treatment on outcome after vaccine‐induced thrombotic thrombocytopenia.